Utrwalona praktyka rozstrzygania spraw w ogólnym postępowaniu administracyjnym - Kwiatek, Błażej (Kwartalnik Prawa Publicznego, 2017)
The principle of legal certainty (the principle of legitimate expectations) was included expressis verbis in article 8 § 2 of the Code of Administrative Procedure. Application of this principle is subject to the occurrence of similar factual and legal circumstances, as well as the existence of a settled practice of dealing with cases. Whereas justified reasons constitute a condition allowing the public administration body to withdraw from the settled practice of dealing with cases. The settled practice is shaped by the public administration body. However, the case law of the administrative courts may have significant implications for the formation of this practice.